1990
DOI: 10.1093/nar/18.19.5677
|View full text |Cite
|
Sign up to set email alerts
|

The promoter of the human parathyroid hormone gene contains a functional cyclic AMP-response element

Abstract: We have screened the sequence of the 394 base pairs upstream of the main transcriptional start site of the promoter of the human parathyroid hormone (PTH) gene for well-known protein recognition motifs with the aim to identify potential positive or negative regulatory elements. Within this region we found a potential cAMP-response element (CRE) besides several other putative binding sites for transcription factors. We fused promoter regions that contain this element and extend beyond the transcription start si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Nonspecific binding was determined from experiments in presence of 100-fold molar excess of unlabelled retinoic acid or with bacterial extracts free of receptor protein obtained from LC137xpGPl-2. Scatchard analysis was performed as described by Scatchard (1949).…”
Section: Retinoid Binding Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Nonspecific binding was determined from experiments in presence of 100-fold molar excess of unlabelled retinoic acid or with bacterial extracts free of receptor protein obtained from LC137xpGPl-2. Scatchard analysis was performed as described by Scatchard (1949).…”
Section: Retinoid Binding Assaymentioning
confidence: 99%
“…Gel-retardation assays (Fried and Crothers, 1981) were performed as described earlier (Rupp et al, 1990). The painvise complementary oligonucleotides of the hormoneresponsive element of the human osteocalcin gene promoter, OC (Schiile et al, 1990) …”
Section: Gel-retardation Assaymentioning
confidence: 99%
“…A major limitation to identifying such regulatory elements, or confirming their functional relevance, has been the lack of suitable parathyroid cell lines that faithfully represent the parathyroid chief cell phenotype, namely the ability to synthesize and secrete PTH, both at a basal level and in response to known physiological regulators such as 1, 25-dihydroxyvitamin D3 (1,25-(OH) 2 D 3 ) and ionic calcium. Previous examinations of the PTH promoter region have identified DNA response elements for the vitamin D receptor (24), calcium (25–27), cyclic-AMP (28) and a yet unknown transcription factor (29). Recent studies have identified conserved DNA elements in the immediate upstream PTH promoter region, which bind to transcription factors Sp1, Sp3 and nuclear factor-Y (3032).…”
Section: Introductionmentioning
confidence: 99%
“…A sequence that resembles the canonical CRE but deviates in one position in the center of the recognition motif is found at position 47. This element, shown to be functional and to confer cAMP-responsiveness, is also present in the rat, bovine and human PTH promoters (Rupp et al 1990). It could be speculated that the modest (approximately two-fold) effect of isoproterenol or forskolin on the promoter activity is due to the deviation from the consensus sequence (TGACGTCA) in the center of the putative CRE (TGACATCA).…”
Section: Discussionmentioning
confidence: 99%